Diversified Resistance Mechanisms in Multi-Resistant Lolium spp. in Three European Countries - Scarabel, Laura; Panozzo, Silvia; Loddo, Donato; Mathiassen, Solvejg K.; Kristensen, Michael; Kudsk, Per; Gitsopoulos, Thomas; Travlos, Ilias; Tani, Eleni; Chachalis, Dimosthenis; Sattin, Maurizio (Frontiers in Plant Science, 2020)
Annual ryegrass species (Lolium spp.) infest cereal crops worldwide. Ryegrass populations with multiple resistance to the acetyl coenzyme A carboxylase (ACCase) and acetolactate synthase (ALS) inhibitors are an increasing problem in several European countries. We investigated the resistance pattern and level of resistance in ryegrass populations collected in Denmark, Greece and Italy and studied the diversity of mechanisms endowing resistance, both target-site and metabolism based. All populations showed high resistance indexes (RI) to the ALS inhibitors, iodosufuron-methyl-sodium + mesosulfuron-methyl (RI from 8 to 70), whereas the responses to the two ACCase inhibitors, clodinafop-propargyl and pinoxaden, differed. The Greek and Italian populations were moderately to highly resistant to clodinafop (RI>8) and showed low to moderate resistance to pinoxaden (RI ranged from 3 to 13) except for one Italian population. In contrast, the Danish Lolium populations showed low to moderate resistance to clodinafop (RI ranged from 2 to 7) and only one population was resistant to pinoxaden. Different mutant ACCase alleles (Leu1781, Cys2027, Asn2041, Val 2041, Gly2078, Arg2088, Ala2096) and ALS alleles (Gly122, Ala197, Gln197, Leu197, Ser197, Thr197, Val205, Asn376, Glu376, Leu574) endowing resistance were detected in the Greek and Italian populations. In several plants, no mutated ALS and ACCase alleles were found showing a great heterogeneity within and among the Greek and Italian populations. Conversely, no mutant ACCase alleles were identified in the four Danish populations and only one mutant ALS allele (Leu574) was detected in two Danish populations. The expression level of nitronate monooxygenase (NMO), glutathione S-transferase (GST) and cytochrome P450s (CYP72A1 and CYP72A2) varied broadly among populations and individual plants within the populations. Constitutive up-regulation of GST, CYP72A1 and CYP72A2 was detected in resistant plants respect to susceptible plants in one Danish and one Italian population. It appears that the mechanisms underlying resistance are rather complex and diversified among Lolium spp. populations from the three countries, coevolution of both target-site resistance and metabolic based herbicide resistance appears to be a common feature in Denmark and Italy. This must be considered and carefully evaluated in adopting resistance management strategies to control Lolium spp. in cereal crops.